2019
DOI: 10.1080/09687688.2019.1597194
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between MassARRAY and pyrosequencing for CYP2C19 and ABCB1 gene variants of clopidogrel efficiency genotyping

Abstract: Clopidogrel is one of the most frequently used drugs in patients to reduce cardiovascular events. Since patients with different genetic variations respond quite differently to clopidogrel therapy, the related genetic testing plays a vital role in its dosage and genetic testing related to clopidogrel therapy is currently considered as routine test worldwide. In this study, we aim to use two different methods MALDI-TOF mass spectrometry and pyrosequencing to detect gene variant of CYP2C19 and ABCB1. Six single n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…In this study, no TT genotype sample was found in the 93 samples. The genotype and allele frequencies of CYP2C19*17 in our study were very similar to those of two Chinese populations . The results of T‐ARMS‐PCR and DNA sequencing were completely consistent, which further confirmed the reliability of the T‐ARMS‐PCR for CYP2C19*17 genotyping.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In this study, no TT genotype sample was found in the 93 samples. The genotype and allele frequencies of CYP2C19*17 in our study were very similar to those of two Chinese populations . The results of T‐ARMS‐PCR and DNA sequencing were completely consistent, which further confirmed the reliability of the T‐ARMS‐PCR for CYP2C19*17 genotyping.…”
Section: Discussionsupporting
confidence: 84%
“…Primers FO, RI, and RO in Table were designed by PRIMER1 online software, and primer FI was from Scott et al T‐ARMS‐PCR was performed in a total volume of 10 μL, including 5 μL of 2 × Taq master mix, 0.4 μM of primer FO, 0.4 μM of primer RI, 0.8 μM of primer FI, 0.4 μM of primer RO, 1 μL of DNA template (including genomic DNA and plasmid DNA), and 2 μL of ddH 2 O. The PCR conditions started with the initial denaturation at 94℃ for 3 minutes, 35 cycles of 94℃ for 20 seconds, 56℃ for 20 seconds, and 72℃ for 20 seconds, followed by a final extension at 72℃ for 5 minutes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before use, SLCO1B1 (rs4149056, 521T>C), CYP2C19*2 (rs4244285, c.681G>A), and CYP2C19*3 (rs4986893, c.636G>A) were detected to ensure the best treatment was administered [21][22][23]. In this study, the SNPs of these genes were detected by a Agena Bioscience MassARRAY system, which had the advantages of detecting dozens of gene loci in one sample [24], requiring fewer samples, having a lower cost, and obtaining results in a shorter time than the Sanger sequencing method [28]. The results showed that there were three genotypes associated with SLCO1B1 (521TT, 521TC, 521CC), CYP2C19*2 (681GG, 681GA, 681AA) and two genotypes associated with CYP2C19*3 (636GG, 636GA) in these 208 CHD patients (Figure 1B).…”
Section: Discussionmentioning
confidence: 99%
“…The process does not require labeling the primers as it measures the molecular weight differences after primer extension [32,33]. Compared to pyrosequencing and other costly sequencing methods, it can provide a cost-efficient option for accurate targeted genotyping in guided drug therapy [34][35][36]. MLPA is a semiquantitative PCR-based method that is suitable for the assessment of genetic loci for detection of CNVs in several types of disorders [37].…”
Section: Pcr-based Genetic Testingmentioning
confidence: 99%